A LEGAL ANALYSIS AND SOCIO-ECONOMIC IMPACT OF ONLINE LENDING (FINTECH LENDING) IN INDONESIA: A LITERATURE REVIEW - Gunawan Widjaja (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2026)
The development of financial technology in Indonesia, particularly information technology-based financing services (fintech lending), has experienced exponential growth but has also brought about serious consequences regarding legal aspects and socio-economic impacts. This study aims to analyse the effectiveness of fintech lending regulations in protecting consumers and to identify the positive and negative socio-economic impacts of online lending practices in Indonesia. The research method employed a literature review using a normative and conceptual approach. The findings indicate that although Indonesia has a comprehensive legal framework comprising the Consumer Protection Act, the Personal Data Protection Act, and OJK regulations relating to fintech lending, implementation and enforcement still face serious challenges, particularly in the enforcement of laws against illegal fintech operations, the protection of personal data, and unethical debt collection practices. From a socio-economic perspective, fintech lending has positive impacts in the form of increased financial inclusion and access to finance for MSMEs, but it also gives rise to significant negative impacts such as over-indebtedness, debt traps, psychological pressure, reduced productivity, social stigma, and even the risk of mental health issues and suicide. The gap between the objectives of financial inclusion and the reality on the ground is clearly evident in the dominance of consumer finance over productive finance, as well as the surge in cases of illegal online lending, which continues to rise despite tighter regulations. This study recommends strengthening coordination between regulatory bodies, more rigorous law enforcement against illegal fintech, improving public financial and legal literacy, and strict oversight of personal data protection so that fintech lending can function as a means of economic empowerment without compromising legal certainty and social welfare.